Carbon dot corrosion inhibitor based on magnolia leaves as well as preparation method and application of carbon dot corrosion inhibitor
By using magnolia leaves as carbon source and synthesizing carbon point corrosion inhibitors through hydrothermal method, the existing corrosion inhibitors have high cost, complex processes and environmental pollution problems, achieving efficient and environmentally friendly metal protection effects.
Patent Information
- Application Number
- CN202411926220.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The existing corrosion inhibitor synthesis process is costly, complex, non-degradable, and toxic, causing pollution to the environment.
Magnolia leaves are used as carbon source, and carbon spot corrosion inhibitors based on magnolia leaves are synthesized by a one-step hydrothermal method. Unsaturated alcohols in magnolia leaves are used to provide C-N, C-O, and -COOH groups to form a stable corrosion inhibiting film.
It realizes efficient metal protection, reduces synthesis cost and process complexity, and ensures environmental protection and low toxicity, solving the environmental pollution problem of existing corrosion inhibitors.
Smart Images

Figure CN119710709A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal material protection, and in particular to a magnolia leaf-based carbon dot corrosion inhibitor, and a preparation method and application thereof. Background Art
[0002] Metal corrosion is a common phenomenon in industrial production. It can cause huge economic losses and safety hazards to water system equipment. At present, the simplest and most cost-effective way to solve the problem of metal corrosion is to add corrosion inhibitors to the corrosive solution in contact with the metal. Therefore, the development of environmentally friendly, green and efficient corrosion inhibitors has become a research hotspot.
[0003] Carbon dots (CDs), as a new type of zero-dimensional carbon-based luminescent nanomaterials, have been widely used in various fields such as bioimaging, energy storage, biosensing, biocatalysis, biomedicine, etc. due to their excellent optical properties, electronic properties, strong fluorescence and low toxicity. CDs have also been proven to be a new type of green corrosion inhibitor in the field of corrosion protection. However, existing corrosion inhibitors have the problems of complex synthesis process and high cost, as well as non-degradability and toxicity, which cause environmental pollution. Summary of the invention
[0004] The object of the present invention is to provide a magnolia leaf-based carbon dot corrosion inhibitor and a preparation method and application thereof. The carbon dot corrosion inhibitor has excellent anti-corrosion performance and is simple to prepare, low in cost and pollution-free.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a carbon dot corrosion inhibitor based on magnolia leaves, comprising the following steps:
[0007] The magnolia leaves are dried and ground in sequence to obtain magnolia leaf powder;
[0008] Mixing the magnolia leaf powder with water, extracting, filtering, and obtaining a liquid phase material;
[0009] The liquid phase material is subjected to a hydrothermal reaction, and the obtained product is sequentially subjected to centrifugal separation, dialysis and freeze-drying to obtain a magnolia leaf-based carbon dot corrosion inhibitor.
[0010] Preferably, the ratio of the magnolia leaf powder to water is 10-50 g:1L.
[0011] Preferably, the extraction temperature is 20-30°C and the extraction time is 20-60 minutes.
[0012] Preferably, the temperature of the hydrothermal reaction is 180-200° C., and the time is 8-24 hours.
[0013] Preferably, the molecular weight cutoff of the membrane used for the dialysis is 1 kDa, and the dialysis time is 24 to 48 hours.
[0014] Preferably, the freeze-drying temperature is -20 to -30°C and the time is 24 to 48 hours.
[0015] The present invention provides a magnolia leaf-based carbon dot corrosion inhibitor prepared by the preparation method described in the above technical solution.
[0016] The present invention provides the application of the magnolia leaf-based carbon dot corrosion inhibitor described in the above technical solution in the field of metal protection in marine environment.
[0017] Preferably, the application method comprises the following steps: mixing the magnolia leaf-based carbon dot corrosion inhibitor with marine environment concrete pore fluid.
[0018] Preferably, the concentration of the magnolia leaf-based carbon dot corrosion inhibitor in the pore fluid of concrete in a marine environment is 25-200 mg / L.
[0019] The present invention provides a method for preparing a carbon dot corrosion inhibitor based on magnolia leaves. The magnolia leaves are used as a carbon source and the carbon dot corrosion inhibitor is synthesized by a one-step hydrothermal method. The magnolia leaves contain unsaturated alcohols, which can provide a large amount of CN, CO, and -COOH groups as a carbon source, and these groups can form a stable corrosion-inhibiting film on the surface of carbon steel to prevent the corrosion of carbon steel, thereby improving the corrosion resistance. The carbon dot corrosion inhibitor based on magnolia leaves prepared by the present invention can be used for the corrosion inhibition of metals (especially carbon steel) under the conditions of concrete pore fluid in a marine environment. The corrosion inhibitor of the present invention has the advantages of low dosage and good corrosion inhibition performance, and at the same time has the characteristics of good stability possessed by the carbon dots themselves, solving the problems of high cost, complex process, non-degradability, toxicity, and environmental pollution of the existing corrosion inhibitor synthesis process.
[0020] The present invention adopts green plants with biodegradability and wide sources as the source of corrosion inhibitor, which ensures the advantages of biodegradability and low cost. In addition, the corrosion inhibitor made from plants is non-toxic and harmless to the environment when used. The impact on the environment during the synthesis, preparation or extraction of the corrosion inhibitor is small or even no impact. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a Fourier transform infrared spectrum of the carbon dot corrosion inhibitor prepared in Example 1;
[0022] Figure 2 This is a transmission electron microscope image of the carbon dot corrosion inhibitor prepared in Example 1;
[0023] Figure 3Nyquist plot (a) and Bode plot (b) of Q235 carbon steel immersed in 3.5wt% NaCl saturated Ca(OH)2 environment for 1.5h with different concentrations of carbon dot corrosion inhibitor;
[0024] Figure 4 Nyquist plot (a) and Bode plot (b) of Q235 carbon steel immersed in 3.5wt% NaCl saturated Ca(OH)2 environment for different time with 100mg / L carbon dot corrosion inhibitor;
[0025] Figure 5 (a) is the polarization curve of Q235 carbon steel immersed in a saturated Ca(OH)2 environment of 3.5wt% NaCl for 1.5h with different concentrations of carbon dot corrosion inhibitor; (b) is the polarization curve of Q235 steel immersed in a saturated Ca(OH)2 environment of 3.5wt% NaCl for different time with 100mg / L carbon dot corrosion inhibitor;
[0026] Figure 6 (a) is the SEM image of the sample surface of Q235 carbon steel sample after being immersed in a saturated Ca(OH)2 environment of 3.5wt% NaCl for 4 days; (b) is the SEM image of the sample surface of Q235 carbon steel sample after being immersed in a saturated Ca(OH)2 environment of 3.5wt% NaCl containing 100mg / L carbon dot corrosion inhibitor for 4 days. DETAILED DESCRIPTION
[0027] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0028] The present invention provides a method for preparing a carbon dot corrosion inhibitor based on magnolia leaves, comprising the following steps:
[0029] The magnolia leaves are dried and ground in sequence to obtain magnolia leaf powder;
[0030] Mixing the magnolia leaf powder with water, extracting, filtering, and obtaining a liquid phase material;
[0031] The liquid phase material is subjected to a hydrothermal reaction, and the obtained product is sequentially subjected to centrifugal separation, dialysis and freeze-drying to obtain a magnolia leaf-based carbon dot corrosion inhibitor.
[0032] The present invention has no particular limitation on the source of the magnolia leaves, which can be obtained in a manner well known in the art.
[0033] The present invention preferably uses ultrapure water to wash fresh magnolia leaves, and then dries and grinds them into powder. The present invention has no special limitation on the drying and grinding, and can be carried out according to the process known in the art; in the embodiment of the present invention, the drying is carried out at 333-343K for 48 hours to eliminate moisture.
[0034] The present invention has no particular limitation on the particle size of the magnolia leaf powder, which can be adjusted according to actual needs.
[0035] In the present invention, the usage ratio of the magnolia leaf powder to water is preferably 10-50g:1L, more preferably 20-30g:1L; the extraction temperature is preferably 20-30°C, more preferably 25°C, and the extraction time is preferably 20-60min, more preferably 30-40min.
[0036] After the extraction, the present invention filters the obtained product to remove leaf residues, obtains the liquid phase material, puts it into a hydrothermal synthesis reactor, and performs hydrothermal reaction in an oven.
[0037] In the present invention, the temperature of the hydrothermal reaction is preferably 180-200° C., more preferably 200° C., and the time is preferably 8-24 h, more preferably 12-15 h.
[0038] The present invention has no particular limitation on the centrifugal separation, and the centrifugal separation may be performed according to a process well known in the art.
[0039] In the present invention, the molecular weight cutoff of the membrane used for dialysis is preferably 1 kDa, the dialysis time is preferably 24 to 48 hours, more preferably 36 to 48 hours; during the dialysis process, water is replaced more than 3 times a day. The present invention removes impurities by dialysis.
[0040] In the present invention, the freeze-drying temperature is preferably -20 to -30°C, and the time is preferably 24 to 48 hours, more preferably 24 hours.
[0041] The present invention provides a magnolia leaf-based carbon dot corrosion inhibitor prepared by the preparation method described in the above technical solution.
[0042] The present invention provides the application of the magnolia leaf-based carbon dot corrosion inhibitor described in the above technical solution in the field of metal protection in marine environment.
[0043] In the present invention, the application method preferably comprises the following steps: mixing the magnolia leaf-based carbon dot corrosion inhibitor with marine environment concrete pore fluid.
[0044] The present invention has no special limitation on the pore fluid of the marine environment concrete, which can be obtained in a manner well known in the art. In an embodiment of the present invention, a saturated Ca(OH)2 solution containing 3.5wt% NaCl is specifically used as a simulated liquid for the pore fluid of the marine environment concrete.
[0045] In the present invention, the concentration of the magnolia leaf-based carbon dot corrosion inhibitor in the pore fluid of concrete in a marine environment is preferably 25 to 200 mg / L, more preferably 50 to 100 mg / L.
[0046] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0047] Example 1
[0048] The magnolia leaves were washed with deionized water, then dried at 333K for 48 h, and the dried leaves were crushed into powder to obtain magnolia leaf powder;
[0049] 2 g of the obtained magnolia leaf powder was added to 100 mL of deionized water, and magnetically stirred with a magnetic stirrer at room temperature for 30 minutes. The leaf residue was removed by filtering with filter cotton, and the obtained liquid phase material was placed in a hydrothermal synthesis reactor, and the reactor was placed in an oven at 200°C for 12 hours. The solution after the reaction was centrifugally filtered and then dialyzed with a 1 kDa membrane for 48 hours. During the dialysis process, the water was replaced more than 3 times a day, and the obtained light yellow solution was freeze-dried in a freeze dryer at -30°C for 24 hours to obtain a brown carbon dot corrosion inhibitor based on magnolia leaves.
[0050] Example 2
[0051] The magnolia leaves were washed with deionized water, then dried at 343 K for 48 h, and the dried leaves were crushed into powder to obtain magnolia leaf powder;
[0052] 5 g of the obtained magnolia leaf powder was added to 100 mL of deionized water, and magnetically stirred with a magnetic stirrer at room temperature for 60 min. The leaf residue was removed by filtering with filter cotton, and the obtained liquid phase material was placed in a hydrothermal synthesis reactor, and the reactor was placed in an oven at 180°C for 24 h. The solution after the reaction was centrifugally filtered and then dialyzed with a 1 kDa membrane for 48 h. During the dialysis process, the water was replaced more than 3 times a day, and the obtained brown-yellow solution was freeze-dried in a freeze dryer at -30°C for 48 h to obtain a brown-yellow carbon dot corrosion inhibitor based on magnolia leaves.
[0053] Test Case
[0054] Application of the carbon point corrosion inhibitor prepared in Example 1 to Q235 carbon steel in the pore fluid of marine environment concrete, using a saturated Ca(OH)2 solution containing 3.5wt% NaCl as a simulated liquid for the pore fluid of marine environment concrete;
[0055] The carbon dot corrosion inhibitor prepared in Example 1 was dissolved in a saturated Ca(OH)2 solution containing 3.5 wt% NaCl, wherein the concentration of the carbon dot corrosion inhibitor ranged from 25 to 200 mg / L.
[0056] The anti-corrosion performance of carbon dot corrosion inhibitor was tested by electrochemical method and surface morphology method:
[0057] Electrode preparation: The cut Q235 carbon steel (2cm×2cm×0.2cm) was placed in a homemade degreasing solution (a mixture of 30g / L sodium carbonate, 30g / L trisodium phosphate, and 15g / L trisodium silicate) heated to 70°C for 10 minutes, and the oil on the surface of the iron sheet was removed by the emulsification reaction and saponification reaction of the homemade degreasing solution on the grease. The iron sheet was then immersed in deionized water for 10 minutes to obtain an oil-free iron sheet; the iron sheet was then placed in 125mL / L HCl for 10 minutes to remove the oxide film on the surface of the iron sheet, and the iron sheet was then immersed in deionized water for 10 minutes to remove the hydrochloric acid solution remaining on the surface of the iron sheet; finally, the iron sheet was placed in an ultrasonic ethanol solution (a mixture of 50% ethanol and 50% water by volume) for cleaning for 10 minutes, and the cavitation effect of the ultrasound was used to accelerate the removal of the dirt layer on the surface of the iron sheet, thereby obtaining a clean and oil-free iron sheet as an iron electrode.
[0058] In the electrochemical process, the corrosion solution was a saturated Ca(OH)2 solution containing 3.5 wt% NaCl.
[0059] Preparation of marine environment concrete pore fluid: The carbon dot corrosion inhibitor prepared in Example 1 was dispersed in a saturated Ca(OH)2 solution containing 3.5 wt% NaCl to obtain solutions of 25 mg / L, 50 mg / L, 100 mg / L, and 200 mg / L carbon dot corrosion inhibitor, respectively.
[0060] Electrochemical testing:
[0061] Electrochemical impedance spectroscopy (EIS) was performed on an electrochemical workstation (CHI660E, Shanghai Chenhua Instrument Co., Ltd.) with a saturated calomel electrode (SCE), a platinum sheet as the counter electrode, and an iron sheet as the working electrode (working area 1 × 1 cm 2 ). The scanning frequency range is 10 -2 Hz~10 5 Hz, EIS data were fitted by Zsimpwin software. The surface properties of iron electrode and the kinetics of carbon dot corrosion inhibitor adsorption on the iron surface were studied, and electrochemical impedance spectroscopy was performed on iron electrode in carbon dot corrosion inhibitor solutions with different concentrations.
[0062] Figure 1 The Fourier transform infrared spectrum of the carbon dot corrosion inhibitor prepared in Example 1; Figure 1 As shown, 3421cm -1 The peak at 2962 cm corresponds to the stretching vibration of the OH bond. -1 The peak at 2926 cm -1 The peak at 1636 cm -1 and 1462cm -1The peak at 1436 cm corresponds to the NC=O bond, and the stretching vibration of the CN bond corresponds to 1436 cm -1 The peak at 1038 cm -1 The characteristic peak at proves the existence of CO bond.
[0063] Figure 2 The transmission electron microscope image of the carbon dot corrosion inhibitor prepared in Example 1; Figure 2 As shown, the carbon dot corrosion inhibitor is spherical and has a size of 1 to 2 nm, which confirms that the carbon dot corrosion inhibitor is a nanomaterial.
[0064] Figure 3 Nyquist plot (a) and Bode plot (b) of Q235 carbon steel immersed in 3.5wt% NaCl saturated Ca(OH)2 environment for 1.5h with different concentrations of carbon dot corrosion inhibitor; Figure 3 The blank in the middle represents a saturated Ca(OH)2 solution of 3.5wt% NaCl without adding carbon dots corrosion inhibitor. The anti-corrosion ability is evaluated by the capacitance arc radius and low-frequency impedance in the Nyquist plot. Figure 3 As shown, when the concentration of carbon dots corrosion inhibitor increases with the same immersion time of 1.5 h, the capacitance arc and |Z| 0.01HZ The value gradually increases, indicating that the addition of carbon dot corrosion inhibitor inhibits the corrosion of the metal. After adding 100 mg / L of carbon dot corrosion inhibitor, the capacitance arc radius increases significantly and the maximum |Z| 0.01HZ value, indicating that the carbon dot corrosion inhibitor forms an adsorption film on the metal surface, inhibiting the corrosion of the metal. When the concentration of carbon dot corrosion inhibitor increases to 200 mg / L, the capacitance arc becomes smaller and |Z| 0.01HZ The value decreases, mainly because under the condition of high concentration of carbon dot corrosion inhibitor, the protective film formed by the corrosion inhibitor is disordered. It can be concluded that the optimal concentration of carbon dot corrosion inhibitor is 100 mg / L.
[0065] Figure 4 Nyquist plot (a) and Bode plot (b) of Q235 carbon steel immersed in a saturated Ca(OH)2 environment with 3.5wt% NaCl for different time periods with 100mg / L carbon dot corrosion inhibitor. Figure 4 As shown, with the increase of immersion time, the capacitance arc and |Z| of the sample immersed in 100 mg / L corrosion inhibitor solution 0.01HZ The value gradually increases, mainly due to the formation of the passive film on the carbon steel surface and the adsorption of Ma-CDs on the metal surface. It reaches the peak after immersion for 1.5 hours, indicating that the adsorption of Ma-CDs on the metal surface plays a major role and forms a relatively complete adsorption film on the metal surface around 1.5 hours. With the increase of immersion time, when the immersion time is 2 hours, the capacitance arc radius decreases, indicating that the metal surface is affected by Cl -As the concentration of Ma-CDs increases and the immersion time prolongs, the phase angle becomes higher and wider. These results confirm that the carbon dot corrosion inhibitor prepared in Example 1 has an effective inhibitory ability to reduce the corrosion of carbon steel in a saturated Ca(OH)2 solution medium containing 3.5wt% NaCl.
[0066] The conventional equivalent circuit diagram was used to fit the EIS parameters of carbon dot corrosion inhibitors with different concentrations when immersed in a saturated Ca(OH)2 solution of 3.5 wt% NaCl for 1.5 h. The fitted parameters are shown in Table 1.
[0067] Table 1 Fitting EIS parameters of carbon dots with different concentrations of corrosion inhibitors immersed in 3.5wt% NaCl saturated Ca(OH)2 environment for 1.5h
[0068]
[0069] As shown in Table 1, under the condition of immersion for 1.5 h, after the introduction of the corrosion inhibitor, R ct and R f The values of R ct The value increases, these results show that the addition of carbon dots corrosion inhibitor forms an adsorption film on the surface of carbon steel, which effectively inhibits the corrosion of carbon steel. These results are consistent with the electrochemical test results, supporting the credibility of the electrochemical data.
[0070] Figure 5 (a) is the polarization curve of Q235 carbon steel immersed in a saturated Ca(OH)2 environment of 3.5wt% NaCl for 1.5h with different concentrations of carbon dot corrosion inhibitor; (b) is the polarization curve of Q235 steel immersed in a saturated Ca(OH)2 environment of 3.5wt% NaCl for different time with 100mg / L carbon dot corrosion inhibitor; Figure 5 The blank in (a) represents a saturated Ca(OH)2 solution containing 3.5 wt% NaCl without adding carbon dots corrosion inhibitor. Figure 5 As shown in the figure, the increase in immersion time leads to a decrease in current density, and the Tafel curve moves in the positive direction, indicating that the increase in corrosion inhibitor inhibits the corrosion of the metal. In addition, the cathode part of the Tafel curve in the corrosion inhibitor solution is parallel to the blank sample, indicating that the corrosion inhibitor has little effect on the cathode reaction mechanism. In the anode part of the Tafel curve, the increase in corrosion inhibitor leads to an increase in the anode slope, indicating that the anode reaction is mainly inhibited.
[0071] Q235 carbon steel samples (0.5 cm × 0.5 cm × 0.5 cm) were immersed in 3.5 wt% NaCl saturated Ca(OH)2 solution without carbon dot corrosion inhibitor and with 100 mg / L carbon dot corrosion inhibitor for 4 days and then FE-SEM test was performed. Figure 6 .
[0072] Figure 6 (a) is a surface SEM image of a Q235 carbon steel sample after being immersed in a saturated Ca(OH)2 environment with 3.5wt% NaCl for 4 days; (b) is a surface SEM image of a Q235 carbon steel sample after being immersed in a saturated Ca(OH)2 environment with 3.5wt% NaCl containing 100mg / L carbon dot corrosion inhibitor for 4 days. Figure 6 As shown, the unprotected sample of Q235 carbon steel sample after being immersed in the corrosion solution for 4 days ( Figure 6 (b)) is severely corroded, with corrosion products and cracks. On the contrary, after adding carbon point corrosion inhibitor, the surface of Q235 carbon steel ( Figure 6 The sample in (a) is relatively smooth and does not contain any corrosion products.
[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a carbon dot corrosion inhibitor based on magnolia leaves, characterized in that: The following steps are involved: The magnolia leaves are dried and ground in sequence to obtain magnolia leaf powder; Mixing the magnolia leaf powder with water, extracting, filtering, and obtaining a liquid phase material; The liquid phase material is subjected to a hydrothermal reaction, and the obtained product is sequentially subjected to centrifugal separation, dialysis and freeze-drying to obtain a magnolia leaf-based carbon dot corrosion inhibitor.
2. The preparation method according to claim 1, characterized in that: The dosage ratio of the magnolia leaf powder to water is 10-50g:1L.
3. The preparation method according to claim 1 or 2, characterized in that: The extraction temperature is 20-30°C and the extraction time is 20-60 minutes.
4. The preparation method according to claim 3, characterized in that: The temperature of the hydrothermal reaction is 180-200° C., and the time is 8-24 hours.
5. The preparation method according to claim 1, characterized in that: The molecular weight cutoff of the membrane used for the dialysis is 1 kDa, and the dialysis time is 24 to 48 hours.
6. The preparation method according to claim 1, characterized in that: The freeze-drying temperature is -20 to -30°C and the time is 24 to 48 hours.
7. The magnolia leaf-based carbon dot corrosion inhibitor prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the magnolia leaf-based carbon dot corrosion inhibitor according to claim 7 in the field of metal protection in marine environments.
9. The use according to claim 8, characterized in that: The application method comprises the following steps: mixing the magnolia leaf-based carbon dot corrosion inhibitor with marine environment concrete pore fluid.
10. The use according to claim 9, characterized in that: The concentration of the magnolia leaf-based carbon dot corrosion inhibitor in the pore fluid of concrete in a marine environment is 25-200 mg / L.